The meaning of global rules of leading trade with particular focus on MFN for developing countries - Domiter, Małgorzata (Economics of the 21st Century, 2014)
This article is an attempt to indicate the role of trade politics in enabling particular countries to raise to the sphere of higher value added within the world trade. East Asia has succeeded using this type of politics, whereas Latin America has not. In each developing country, some advantages coming from the liberalization of import, which has been a part of strategy focused on confining poverty and accelerating the accrual, can be noticed. However, the construction of reforms, their sequence and the pace of implementing have decided about the effectiveness of the liberalization strategy. Notwithstanding this, the true economic success has been achieved only by developing countries which use the export growth politics. In the article, three theses are described: 1) foreign trade is a more powerful factor that furthers the development of the poorest countries than foreign aid and the role of the foreign trade increases with the general development of a country1, 2) foreign trade is determined by global rules of its operating, therefore, developing countries have to join in the system of international coordination of trade politics, 3) although MFN is used in a commercial treaty aspiring to regulate even worldwide business relations, the liberalization of the world trade, based on MFN, affects developing countries in a negative way, because with a downturn of general level of imposition, both the distinction and benefit from GSP system for the countries are decreasing
Ekonomia XXI Wieku = Economics of the 21st Century, 2014, Nr 4 (4), s. 9-27
Keywords: trade politics; rules of trade politics; developing countries; MFN; polityka handlowa; reguły polityki handlowej; kraje rozwijające się; KNU